Going from a low to a high employment equilibrium - Marc Lavoie; Eckhard Hein (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
This paper presents an extensive, but non-formalized, critique ofthe concept of the non-accelerating inflation rate of unemployment(NAIRU) and all similar concepts such as the steady-inflation rateof capacity utilization (SIRCU) which are used by mainstream economiststo argue that there is no alternative, and hence that labourmarkets must be made more flexible while governments must abstainfrom engaging in expansionary fiscal policies except underexceptional circumstances. This is followed by the presentation ofan alternative approach of the labour market, based on a more realisticview of the shape of the unit costs of firms, which argue s thatemployment is essentially determined by the extent of sales in thegoods market rather than by some profit-maximization constraint,and that higher real wages will normally generate a rise in domesticaggregate demand and hence a rise in employment. The paperends with a discussion of the implications of such a view for wagebargaining and macroeconomic policies. What is advocated here isa wage-led growth strategy. – – Dieses Papier präsentiert eine ausführliche, jedoch nicht formalisierte, Kritik am Konzept der inflationsneutralen Arbeitslosenquote (NAIRU) und ähnlichen Konzepten wie der stabilen Inflationsrate der Kapazitätsauslastung (SIRCU), die in der vorherrschenden Sicht die vermeintliche Alternativlosigkeit von Arbeitsmarktflexibilisierung und fiskalischer Austerität begründen. Gefolgt wird dies von einem alternativen Ansatz zum Arbeitsmarkt, der auf einer realistischeren Darstellung der Stückkosten der der Firmen beruht. Hierbei wird argumentiert, dass Beschäftigung hauptsächlich durch die Verkäufe auf dem Gütermarkt, anstatt von einer Profitmaximierungsrestriktion bestimmt wird. So führen höhere Reallöhne normalerweise zu einer höheren aggregierten Nachfrage und somit zu einer höheren Beschäftigung. Abschließend werden die Implikationen dieses Ansatzes für Lohnverhandlungen und makroökonomische Politik diskutiert. Dabei wird im Sinne einer Lohn-getragenen Wachstumsstrategie argumentiert.
urn:nbn:de:101:1-2015032510716
Keywords: 330; Natürliche Arbeitslosenquote; Inflationsrate; Arbeitsmarktflexibilität; Verhandlungstheorie des Lohnes; Theorie